2011
DOI: 10.1111/j.2044-8309.2011.02029.x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal investigation of the rejection–identification hypothesis

Abstract: The rejection-identification model (RIM; Branscombe, Schmitt, & Harvey, 1999) is supported by a number of previous studies (e.g., Schmitt, Branscombe, Kobrynowicz, & Owen, 2002; Schmitt, Spears, & Branscombe, 2003). This suggests that rejection by an outgroup can lead minority group members to identify more with their ingroup, thereby buffering them from the negative effects of discrimination. However, contradictory findings have been produced by other research (e.g., Eccleston & Major, 2006; Major, Quinton, &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 64 publications
(125 reference statements)
6
77
0
1
Order By: Relevance
“…SIT researchers have also found that the sense of social integration and connectedness that accompanies group membership is negatively related to depression (Cruwys, Haslam, Dingle, Haslam, & Jetten, 2014;Kawachi & Berkman, 2001;Ramos, Cassidy, Reicher, & Haslam, 2012). Social identification taps into this sense of social connectedness and has been shown to support psychological well-being (Elliott & Doane, 2015;Greenaway, Cruwys, S. A. Haslam, & Jetten, 2016;Khan et al, 2014;Sani, Herrera, Wakefield, Boroch & Gulyas, 2012).…”
Section: The Buffering Hypothesismentioning
confidence: 99%
“…SIT researchers have also found that the sense of social integration and connectedness that accompanies group membership is negatively related to depression (Cruwys, Haslam, Dingle, Haslam, & Jetten, 2014;Kawachi & Berkman, 2001;Ramos, Cassidy, Reicher, & Haslam, 2012). Social identification taps into this sense of social connectedness and has been shown to support psychological well-being (Elliott & Doane, 2015;Greenaway, Cruwys, S. A. Haslam, & Jetten, 2016;Khan et al, 2014;Sani, Herrera, Wakefield, Boroch & Gulyas, 2012).…”
Section: The Buffering Hypothesismentioning
confidence: 99%
“…Although these different dimensions of identity are often positively correlated with each other, they have been shown to have differing relationships with the same outcome variables. For example, in a sample of Aboriginal peoples in Canada, identity centrality and in-group affect (i.e., feelings of pride associated with group membership) had opposing positive and negative relationships with perceived discrimination, respectively (Bombay et al, 2010), which has also been reported among other minority populations (Ramos, Cassidy, Reicher, & Haslam, 2012). In effect, the widespread practice of not distinguishing between these dimensions of identity has been suggested to be a main factor in contributing to the many divergent findings reported in studies exploring the relationships between identity, perceived discrimination, and well-being, and highlight the importance of clearly describing which aspect of identity is being considered (Ashmore et al, 2004;Markstrom et al, 2011;Ramos et al, 2012).…”
Section: Ethnic Identity Centralitymentioning
confidence: 94%
“…Therefore, although the more affective and relational aspects of identity often act as protective factors for certain measures of well-being, such as depressive symptoms (Bombay et al, 2010;Brondolo, ver Halen, Pencille, Beatty, & Contrada, 2009;Ramos et al, 2012;SpencerRodgers & Collins, 2006), these benefits can sometimes be mitigated by the fact that minority group members with high levels of identity centrality appear to be more likely to report experiencing high levels of discrimination (Bombay et al, 2010;Sellers, Caldwell, Schmeelk-Cone, & Zimmerman, 2003;SpencerRodgers, & Collins, 2006).…”
Section: Ethnic Identity Centralitymentioning
confidence: 95%
“…Discrimination may lead minority group members to identify more with their group to alleviate the adverse effects on well-being of rejection by a dominant group (the rejectionidentification hypothesis; Branscombe et al 1999;Ramos et al 2012). Conversely, a stronger racial identity increases awareness of discrimination (Sellers and Shelton 2003), in line with Thoits's (2013) identityrelevant stressor hypothesis.…”
Section: Control Variablesmentioning
confidence: 99%